Antifilarial potential of the fruits and leaves extracts of Pongamia pinnata on cattle filarial parasite Setaria cervi - Ahmed, Qamar Uddin; Parveen, Nazneen; Khan, Nizam Ud Din; Singhal, Kavita C. (John Wiley & Sons Inc., USA., 2003)
The effect of aqueous and alcohol extracts of the fruits and leaves of Pongamia pinnata (Linn.) Merr. (Syn. Pongamia glabra Vent, leguminosae) on the spontaneous movements of both the whole worm and the nerve–muscle preparation of Setaria cervi and on the survival of microﬁlariae in vitro was studied. The aqueous and alcohol extracts of fruits and the alcohol extract of leaves caused an inhibition of spontaneous movements of the whole worm and the nerve–muscle preparation of S. cervi. The initial stimulatory effect was not observed with the aqueous extract of fruits on the nerve–muscle preparation. The concentration required to inhibit the movements of the whole worm preparation was 250 µg/mL for aqueous, 120 µg/mL for alcohol extract of fruits and 270 µg/mL for alcohol extracts of the leaves. The concentrations of P. pinnata extracts required to produce an equivalent effect on the nerve–muscle preparation were 25 µg/mL, 5 µg/mL and 20 µg/mL, respectively, suggesting a cuticular permeability barrier.